PENGARUH KARAKTERISTIK TUJUAN ANGGARAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAERAH KABUPATEN SLEMAN - Sulastiningsih Sulastiningsih; Zaenab Alboneh (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2020)
This research aims to analyze the influence of budgetary goal characteristics of participation, clarity, feedback and difficulity on the government performance accountability Sleman district. The number of samples used in the study as many as 98 respondents. Data collection is carried out by the methods of questionnaire. The results of the questionnaires were processed using SPSS Statisctics 18. The results show that budgetary participation and budgetary goal clarity have positive effect on the government performance accountability Sleman district. Meanwhile, the results of budgetary goal difficulity were found that have no effect on the government performance accountability leman district.